Body mass index has no impact on sperm quality but on reproductive hormones levels. (24th November 2012) - M. Al‐Ali, B.; Gutschi, T.; Pummer, K.; Zigeuner, R.; Brookman‐May, S.; Wieland, W. F.; Fritsche, H. M.; Aziz, A.
Summary The influence of overweight and obesity on sperm quality and reproductive hormone levels is under discussion. The aim of the present retrospective study was to evaluate the influence of body mass index (BMI) on sperm quality and reproductive hormones. We analysed semen samples and serum levels of FSH, LH, T and PRL of a total of 2110 men attending our andrology unit from 1994 to 2010 due to infertility work‐up. Patients were stratified according to their BMI in four groups. Main outcome measures were sperm motility, morphology and concentration. Serum levels of FSH, LH, T and PRL were evaluated as well. No statistically significant difference was found for sperm quality and BMI between patients categorised according to the four BMI levels. T (P < 0.001) and LH (P = 0.006) significantly differed between the four groups. In multivariable analysis, BMI did not have significantly independent influence on all assessed sperm quality parameters, whereas BMI significantly influenced hormone values for LH (P = 0.001), T (P = <0.001) and PRL (P = 0.044). We therefore conclude that BMI has no significant impact on sperm quality parameters. However, serum levels of LH, T and PRL were significantly influenced by BMI.